Science process skills and critical thinking skills in inquiry-based learning model with project-based assessment - Rapi, Ni Ketut; Sujanem, Rai; Yasmini, Luh Putu Budi; Setemen, Komang (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of this research is to determine whether or not there are significant improvements in science process skills and critical thinking skills in connection with the use of the inquiry-based learning model with project-based assessment on the topic of heat and fluids. The current levels of students' science process skills and critical thinking skills are still low, and it is important to develop these skills as they influence the way students think and act in solving problems. The inquiry-based learning model with project-based assessment is used to enhance students' science process skills and critical thinking skills. This research employed a pretest-posttest Non-equivalent Control Group Design. The study involved a population of 10th-grade students at State Senior High Schools in Singaraja, with a sample size of 159 students. Data were collected using tests for science process skills and critical thinking skills. The data analysis techniques included descriptive analysis and multivariate covariance analysis. The analysis results yielded a significance value of < 0.05. In conclusion, there are differences in science process skills and critical thinking skills, both simultaneously and partially, between the experimental group and the control group. The findings have confirmed that the inquiry-based learning model with project-based assessment is effective in improving science process skills and critical thinking skills, making it an optimal choice for addressing challenges in physics education.